(untitled) (Quinto Sol, 2023)
This paper aims to address some consequences of immigration in relation to the exercise of motherhood between 1900 and 1930 in Buenos Aires. Through a case study we explore the experiences of a migrant mother who decided, under particular circumstances, to place her children in children’s homes. Far from being an exception, this case expresses the experiences of other women who were diagnosed with various mental illnesses in which a deviation in "affectivity" and behavior towards the family nucleus with emphasis on the children appears as a symptom. Through the interweaving of sources that include medical records of the Asilo de Alienadas de Lomas de Zamora and files of minors of the Sociedad de Beneficencia, this article proposes to account for both the emotional prescriptions within the medical discourse in relation to the exercise of motherhood, as well as the emotional experiences of women who went through the path of medicalization and confinement. In the children’s files it is possible to trace evidence of their experiences but also the agency, the motivations and the meaning of motherhood and care that a mother deployed in a context of vulnerability produced by migration.